269 Clinical profiles and intraoperative characteristics after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy– an experience from a tertiary care centre in India. (13th November 2020) - Kumar, N; Ray, MD; Deo, S
Abstract : Introduction: Peritoneal surface malignancies were considered as terminal disease before the introduction of cytoreduction surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC). Methods: Ninety-seven patients underwent CRS and HIPEC from 2017 – 2019 and data was recorded from a prospective maintained computerized database. Clinical profile, Peritoneal Cancer Index (PCI), Completeness of Cytoreduction (CC), CRS Operative time and HIPEC time were reviewed. Results: Demographic characteristics- The median age was 57 years (range; 25–65 years). Females comprised 70% of the population. The median body mass index was 27.21 (Range; 25–39). Disease distribution- Ovarian cancer comprised of 58.76%, Colorectal constituted 32% and appendiceal cancer accounted for 9.2%. High-grade histology was found in 76 patients. PCI & CC Score characteristics- Median Peritoneal Cancer Index (PCI) was 14 (range; 8–25). Completeness of Cytoreduction (CC) of 0 and 1 was achieved in all patients, with CC -0 in 87 patients (90%) and CC-1 in 10 patients (10%). The mean operating time for CRS was 581 minutes (range; 172–874) and for HIPEC was 59.58 minutes (range; 45 – 60). The extent of resection- Right hemicolectomy along with anterior peritonectomy was done in 14 patients. Low Anterior Resection with pelvic peritonectomy was done in 10 patients. Total omentectomy, cholecystectomy and segmental ureteric resection were performed in 57, 10 and 3 patients respectively. Conclusions: Complete CRS and HIPEC are safely done with expert hands in selected patients. The intraoperative extent of disease and complete CRS along with the duration of surgery and chemotherapeutic drug dosage are important determinants of peri-perioperative outcomes.